Association between non-alcoholic fatty liver disease and urolithiasis on non-contrast computed tomography: a systematic review and meta-analysis / Raisuha Syuhadah Abdul Rahim, Noor Shafini Mohamad - Abdul Rahim, Raisuha Syuhadah; Mohamad, Noor Shafini (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
There is growing evidence that non-alcoholic fatty liver disease (NAFLD) is associated with urolithiasis. NAFLD could be a predisposing factor for urolithiasis. However, this association has been unclear and inconsistent. Thus, this study was conducted to review the existing studies that compared the risk of urolithiasis in patients with NAFLD to patients without NAFLD detected on non-contrast computed tomography (CT). A comprehensive literature review was carried out using leading journal databases including Scopus, Dimensions, Web of Sciences, and Science Direct, to identify all related studies. The review method was guided by PRISMA statement as reporting guidelines and standards in the current study to ensure the review reported is with a high level of details. The literature search resulted in four studies with 2,999 individuals who fulfilled the eligibility criteria and were included in the analysis. NAFLD significantly associated with an increased risk of urolithiasis with a pooled odd ratio of 2.83 (95% CI, 1.14-7.00: I2 90%). A significantly increased risk of urolithiasis among patients with NAFLD compared to patients without NAFLD was observed in this meta-analysis. Finally, future studies investigating NAFLD and urolithiasis and its associate factors are needed to allow broader understanding and treatment of the patient's condition.